The Read-Answer-Discuss-Explain-Create (RADEC) Model Assisted by Image Media to Improve Learning to Write Explanatory Texts for Fifth Grade Students - Suryani, Amih; Sulyati, E.; Saepurokhman, Asep (Jurnal Bahasa Indonesia Prima (BIP), 2025)
This research is motivated by the low ability of fifth grade elementary school students in writing explanatory texts. The purpose of this study is to determine the effect of the Read Answer Discuss Explain Create (RADEC) learning model assisted by image media on students' ability to write explanatory texts. This study uses a quantitative approach with a quasi-experimental method and a posttest-only control group design . The research sample consisted of three elementary schools in Sumedang Regency, each with 25 students in the experimental and control classes. The instruments used were post-learning tests and observations. The results showed that the application of the RADEC model assisted by image media significantly improved students' ability to write explanatory texts compared to the conventional model. This can be seen from the higher scores obtained in the experimental class, which indicates that the RADEC model helps students develop critical and creative thinking skills, search for information independently, discuss in groups, and write explanatory texts based on their own experiences and understanding. This study proves the effectiveness of the RADEC model assisted by image media in improving the quality of learning to write explanatory texts in elementary school students.